Molecular characterization of Vibrio cholerae O1 and non-O1 from human and environmental sources in Malaysia - Radu, S.; Ho, Y.K.; Lihan, S.; Yuherman, .; Rusul, G.; Yasin, R.M.; Khair, J.; Elhadi, N. (Cambridge University Press, 1999)
A total of 31 strains of Vibrio cholerae O1 (10 from outbreak cases and 7 from surface water) and non-O1 (4 from clinical and 10 from surface water sources) isolated between 1993 and 1997 were examined with respect to presence of cholera enterotoxin (CT) gene by PCR-based assays, resistance to antibiotics, plasmid pro®les and random amplified polymorphic DNA (RAPD) analysis. All were resistant to 9 or more of the 17 antibiotics tested. Identical antibiotic resistance patterns of the isolates may indicate that they share a common mode of developing antibiotic resistance. Furthermore, the multiple antibiotic resistance indexing showed that all strains tested originated from high risk contamination. Plasmid profile analysis by agarose gel electrophoresis showed the presence of small plasmids in 12 (7 non-O1 and 5 O1 serotypes) with sizes ranging 1±3±4±6 MDa. The CT gene was detected in all clinical isolates but was present in only 14 (6 O1 serotype and 8 non-O1 serotype) isolates from environmental waters. The genetic relatedness of the clinical and environmental Vibrio cholerae O1 and non-O1 strains was investigated by RAPD fingerprinting with four primers. The four primers generated polymorphisms in all 31 strains of Vibrio cholerae tested, producing bands ranging from <250 to 4500 bp. The RAPD profiles revealed a wide variability and no correlation with the source of isolation. This study provides evidence that Vibrio cholerae O1 and non-O1 have significant public health implications.